Adoption Of A Proposed Pilot Program To Enable School Performance In Faculties Of Education/ اعتماد برنامج تجريبي مقترح لتمكين أداء مدرسي في كليات التربية - Talib Sulybe Hussein (Ijaz Arabi Journal of Arabic Learning, 2022)
The subject (Basis of education) is one of the most important educational and psychological subjects in the curricula of the College of Education, and the teacher of this subject is the backbone of the scientific life of these colleges. Those in charge of teaching this vital subject aspire to acquire many professional competencies that enhance their scientific capabilities in teaching. To obtain more educational and psychological experiences necessary in their field of specialization, they make a permanent need for the scientific skills and social characteristics that should be provided by the teacher of the subject (foundations of education) in the classroom.